STRATEGI PENGEMBANGAN USAHA KOPI BUBUK PADA INDUSTRI BUMI MUTIARA DI KOTA PALU - Tundeka, Deswina; Laapo, Alimudin; Howara, Dafina (AGROTEKBIS, 2018)
The aim of this study was to know how appropriate alternative strategies to be applied inthe development of ground coffee on Bumi Mutiara Industry in the city of Palu. The research was conducted on ground coffee Bumii Mutiara Industry located at Jalan Mutiara Palu Palu Nagaya II No.29-30. Number of respondents 5 people consisting of 1 leader, 2 employees, 1 customer, and 1 person perindakop employees. The analysis method is the SWOT analysis. The results showed the total value obtained in the amount of 3.34 IFAS table with a score of 2.20 and the power of weakness score of 1.14 while the total value obtained EFAS, which amounted to 3.08 with a score of 1.80 opportunities and threats score of 1 , 28. Based on calculations of the value of the rating and weighting factors internal business development strategies Bumi Mutiara ground coffee as the X-axis is 1.06, while external factors as the Y-axis is 0.52. The alternative strategy is the right strategy SO. SO strategy is a strategy that can be used ground coffee industry Bumi Mutiara in creating strategies to use force to take advantage of existing opportunities.